Development of a hands‐free electrolarynx for obtaining a human‐like voice using the LPC residual wave. Issue 4 (18th October 2022) - Takeuchi, Masaki; Soejima, Yutaro; Ahn, Jaesol; Lee, Kunhak; Takaki, Ken; Ifukube, Tohru; Yabu, Ken‐Ichiro; Takamichi, Shinnosuke; Sekino, Masaki
Abstract: The conventional electrolarynx (EL) restores the voice of people who have lost their voice, however, its voice sounds like a robot and it occupies user's one hand. Therefore, we developed a hands‐free wearable electrolarynx that improves the voice quality with the LPC residual wave as the vibration sound. Our device was able to reproduce sounds below 500 Hz, which is close to the fundamental frequency, but from 1700 Hz to 4000 Hz, the conventional EL continuously showed a frequency response closer to the spectrum of the user's vocal sound than our device. Thus, the periodic sound of the fundamental frequency band was found to be closer to human speech than individuality or sound quality.